2020
DOI: 10.1080/01478885.2020.1779484
|View full text |Cite
|
Sign up to set email alerts
|

A review on histotechnology practices in COVID-19 pathology investigations

Abstract: COVID-19 disease in humans, caused by the novel SARS-CoV-2 virus, was first reported in the city of Wuhan, China in December 2019. This disease has quickly developed into a global pandemic, resulting in over 350,000 deaths worldwide and over 5 million confirmed infections in a matter of 6 months. Although the genome of this novel viral RNA was sequenced quickly and testing kits were manufactured to assist in combatting COVID-19, the diagnosis and treatment will remain relatively unsuccessful until the patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, animal studies and post-mortem pathological studies of severe viral pneumonia revealed that few intact virions in extensively injured organ tissues and only occasional PCR or histochemical antibody positivivity. [63][64][65] Thus, it is a reasonable assumption that the etiological substances in pneumonia and ARDS in viral infections are produced by certain pathogen-infected cells rather than the pathogen itself. If SARS-CoV-2 is responsible for acute lung injury, researchers should identify the pathogens via lung tap and/or pleural effusion instead of those from the upper or lower respiratory tracts such as nasopharyngeal swab or bronchial lavage fluid, and through a culture method rather than PCR assay.…”
Section: Laboratory Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, animal studies and post-mortem pathological studies of severe viral pneumonia revealed that few intact virions in extensively injured organ tissues and only occasional PCR or histochemical antibody positivivity. [63][64][65] Thus, it is a reasonable assumption that the etiological substances in pneumonia and ARDS in viral infections are produced by certain pathogen-infected cells rather than the pathogen itself. If SARS-CoV-2 is responsible for acute lung injury, researchers should identify the pathogens via lung tap and/or pleural effusion instead of those from the upper or lower respiratory tracts such as nasopharyngeal swab or bronchial lavage fluid, and through a culture method rather than PCR assay.…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…These findings suggest that the etiologic substances of pneumonia and ARDS could be related to the substances derived from the host cells by physical injury or other conditions. In addition, animal studies and postmortem pathological studies of severe viral pneumonia revealed that few intact virions in extensively injured organ tissues and only occasional PCR or histochemical antibody positivity [ 63 - 65 ]. Majority of affected subjects might be PCR negative in the blood even in severe cases.…”
Section: Etiologymentioning
confidence: 99%